Effect of mesenchymal stem cells therapy in experimental kaolin induced syringomyelia model - Bal, Ercan; Hanalioğlu, Şahin; Köprü, Çağla Zübeyde; Köse, Sevil; Başak, Ahmet T.; Pehlivan, Sibel; Çetinkaya, Duygu; Purali, Nuhan; Korkusuz, Petek; Bozkurt, Gökhan (Minerva Medica, 2022)
Background: Syringomyelia is a pathological cavitation of the spinal cord. In this study, we examined whether a syrinx cavity would limit itself with axonal regeneration and stem cell activity in the cavity, and we evaluated subjects on a functional basis.Methods: Groups were designated as kaolin, trauma, kaolin-trauma, and saline groups. Also divided out of the syringomyelia treated groups were those given human mesenchymal stem cells (hMSCs). All groups were evaluated with immunohistochemistry, electron microscopy, confocal microscopy and functionally.Results: The kaolin-trauma group had a significant correction of BBB score with hMSCs therapy. The syrinx cavity measurements showed significant improvement in groups treated with hMSCs. The tissue surrounding the syrinx cavity, however, appeared to be better organized in groups treated with hMSCs. The process of repair and regeneration of damaged axons in the lesion were more improved in groups treated with hMSCs. Using confocal microscopy, fluorescence of hMSCs was observed in the central canal, in the ependymal tissue, and around the lesion.Conclusions: It was concluded that axonal repair accelerated in groups receiving stem cells, and thus, stem cells may be effective in recovery of neural tissue and myelin damage in syringomyelia.
Keywords: Confocal Microscopy; Kaolin; Mesenchymal Stem Cell; Syringomyelia